Aflatoxin M1 in pasteurized, ESL and UHT milk products from central China during summer and winter seasons: Prevalence and risk assessment of exposure in different age groups. (July 2021) - Xiong, Jianglin; Zhang, Xiaofang; Zhou, Hualin; Lei, Mengqi; Liu, Yulan; Ye, Chun; Wu, Wenxuan; Wang, Chong; Wu, Lingying; Qiu, Yinsheng
Abstract: This study aimed to investigate aflatoxin M1 (AFM1) contamination in pasteurized, extended shelf life (ESL) and ultra-high temperature (UHT) milk in central China in winter and summer, and to assess the risk of exposure to milk AFM1 in 10 different age groups. A total of 547 milk samples were collected in Henan, Hubei and Hunan provinces from 2019 to 2020, of which 142 pasteurized milk samples, 68 ESL milk samples and 69 UHT milk samples were collected in summer, and 161 pasteurized milk samples, 79 ESL milk samples and 28 UHT milk samples were collected in winter. The concentrations of AFM1 in these samples were determined by ELISA, with a recovery and relative standard deviation of 95.0–98.6% and 3.31–4.18%, respectively. AFM1 was detected in 431 samples (78.8%) with an average concentration of 19.6 ng/L in positive samples. The AFM1 concentrations in 29 samples (5.3%) were higher than the maximum residue level (MRL) of 50 ng/L set by the EU, but much lower than the value of 500 ng/L set by China. The average concentration of AFM1 (25.4 ng/L) in winter milk was 88.1% higher (p < 0.05) than that (13.5 ng/L) in summer. The concentration of AFM1 in UHT milk was lower (p < 0.05) than that in pasteurized and ESL milk in both winter and summer. Children aged 2–4 years had the highest risk of exposure to AFM1 in milk, with a mean estimated daily intake of 0.22 ng/kg bw/day. Therefore, it is necessary to strictly detect and prevent AFM1 contamination in milk, especially in winter, to reduce the risk of AFM1 exposure in humans. Highlights: The positive rate of AFM1 contamination in liquid milk was 78.8%. All milk samples were below 500 ng/L, with 5.3% of samples above 50 ng/L. The concentration of milk AFM1 in winter was higher than that in summer. AFM1 level in UHT milk was lower than those in pasteurized and ESL milk. Children aged 2–4 years had the highest risk of exposure to milk AFM1.